Mercury-Resistant Bacteria Isolated from an Industrial Effluent Outlet in Iligan City, Philippines - Teves, Franco (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
Water, sediment and soil samples were obtained from an effluent outlet shared by two chemical plants in the western suburb of Iligan City. The samples were screened for mercury-resistant organisms by serial dilution and spread-plating on MS agar medium containing 10 ppm HgCl2. Four bacterial isolates, namely, Bacillus sp., Corynebac:terium sp., Cytophaga sp. and Klebsi.ella sp. were obtained. These isolates were able to tolerate up to .. 40 ppm HgCl2 in the MS agar medium. Comparatively, known cultures from the DBS culture collection tolerated only up to 20 ppm HgCl2 in MS agar medium. Further, the effluent-derived isolates retained their resistance phenotype across several successive colony transfers. This result shows the possession of stable mercury-resistance genes by the isolates. These organisms are therefore, suitable candidates for the biological treatment of mercury containing wastewater and for genetic research.